The Safety of Ethnic Foods in Campania Region: A Preliminary Study - Loredana Biondi; Andrea Fulgione; Assunta De Lella; Anna Cutarelli; Morena Nappa; Francesca Garofalo; Stefania Cavallo; Donatella Nava (Foods, 2023)
Ethnic food is produced by an ethnic group—using their familiarity with local ingredients of plants and/or animal origin—and it is consumed in a country other than the country of origin. In Italy, the ethnic food market has expanded over the last three decades. The aim of this study was to evaluate the correct labeling, the microbiological communities and the allergens present in 50 ethnic foods. The visual inspection of labels and microbiological and allergen analyses have been carried out for evaluating their food safety. The visual inspection of labels revealed the absence of labeling in Italian and/or a failure to specify the place of origin. Microbiological analyses showed the absence of pathogens (i.e., Salmonella spp., Listeria monocytogenes and E. coli 0157:H7) in all matrices, but the presence of process hygiene indicator bacteria (total bacterial count, Coagulase-positive Staphylococci, Bacillus cereus, coliforms, yeasts and molds) was found in 37 samples. With regard to allergens, 12 samples were non-compliant for the presence of at least one allergen, while only two products were of species different from those declared on the label. This research highlights the need to increase the control of ethnic foods and also to improve the labeling system by standardizing international regulations.